(untitled) (Journal of Engineering, 2012)
This research includes the using of statistical to improve the quality of can plastics which is produced at the state company for Vegetable oils (Almaamon factory ) by using the percentage defective control chart ( p-chart ) of a fixed sample. A sample of size (450) cans daily for (30) days was selected to determine the rejected product . Operations research with a (win QSB ) package for ( p-chart ) was used to determine test quality level required for product specification to justify that the process that is statistically controlled. The results show high degree of accuracy by using the program and the mathematical operations (primary and secondary ) which used to draw the control limits charts and to reject the statistically uncontrolled samples . Moreover a final chart was drawn to be used in the factory .The research shows improvement of the can product by percentage (0.06 % ), product defects percentage was lowered from ( 0.53 % to 0.47 % ) for the production process which becomes statistically controlled .Also it was found that it was within Iraqi specification (1093).